Probiotics-derived butyric acid may suppress systemic inflammation in a murine model of chronic obstructive pulmonary disease (COPD) - Pradana, Andika; Sari, Dina K.; Rusda, Muhammad; Tarigan, Amira P.; Wiyono, Wiwien H.; Soeroso, Noni N.; Eyanoer, Putri C.; Amin, Mustafa M. (Narra Sains Indonesia, 2025)
Systemic inflammation in chronic obstructive pulmonary disease (COPD) contributes to multimorbidity and a diminished quality of life. Probiotics, through the gut-lung axis, have shown potential to mitigate systemic inflammation; however, their specific role in COPD-related inflammation remains unclear. The aim of this study was to evaluate the efficacy of probiotics in reducing serum interleukin-6 (IL-6) levels by enhancing butyric acid production in a murine model of COPD. An in vivo experimental study with a post-test-only control group design was conducted using 30 C57BL/6 mice randomized into five groups: non-COPD healthy control, untreated COPD, COPD treated with bronchodilator, COPD treated with probiotics, and COPD treated with a combination of bronchodilator and probiotics. COPD was induced by six weeks of cigarette smoke exposure, followed by six weeks of treatment while continuing the smoke exposure. Caecal butyric acid and serum IL-6 levels were measured using enzyme-linked immunosorbent assay (ELISA) and gas chromatography, respectively. Caecal butyric acid levels were lowest in untreated COPD mice (1.2±0.28 mmol/L) and significantly increased with probiotic administration (6.6±4.43 mmol/L, p=0.010), exceeding levels observed in healthy controls (3.9±2.05 mmol/L). Serum IL-6 levels were highest in COPD-induced mice (19.4±6.71 pg/mL) and significantly reduced with administration of probiotics (13.5±0.43 pg/mL, p=0.035), approaching levels of healthy controls (13.0±2.24 pg/mL, p=0.847). A negative correlation was observed between butyric acid and serum IL-6 levels (r=-0.420; p=0.021), suggesting that higher butyric acid levels were associated with reduced systemic inflammation. These findings demonstrated that probiotics, via their metabolite butyric acid, effectively reduced systemic inflammation in a COPD mouse model, highlighting their potential as a therapeutic approach for managing COPD-related inflammation.